Scenes of violence and sex in recent award-winning LGBT-themed young adult novels and the ideologies they offer their readers. Issue 6 (1st November 2016) - Clark, Caroline T.; Blackburn, Mollie V.
ABSTRACT: This study examines LGBT-inclusive and queering discourses in five recent award-winning LGBT-themed young adult books. The analysis brought scenes of violence and sex/love scenes to the fore. Violent scenes offered readers messages that LGBT people are either the victims of violence-fueled hatred and fear, or, in some cases, showed a gay person asserting agency by imposing violence on a violent homophobe. In contrast, sex and/or love scenes offered readers more nuanced messages about LGBT people. In some sex/love scenes, LGBT people are isolated by homophobia, internalized, or otherwise. In others, though, LGBT people are able to connect better with those who love them as a result of their unlearning or removal of transphobia and/or homophobia. If books with scenes of violence and sex/love are prohibited, then messages about how people connect to and distance themselves from one another by knowing and loving themselves are lost. We argue that teachers and librarians must understand the discourses that shape how they read and discuss LGBT-themed literature and know how to help students navigate these in ways that challenge but do not damage readers; this paper can facilitate such efforts.